Mental health solutions for domestic violence victims amid COVID-19: a review of the literature - Zhaohui Su; Dean McDonnell; Stephanie Roth; Quanlei Li; Sabina Šegalo; Feng Shi; Shelly Wagers (BMC, 2021)
Abstract Background Due to COVID-19, domestic violence victims face a range of mental health challenges, possibly resulting in substantial human and economic consequences. However, there is a lack of mental health interventions tailored to domestic violence victims and in the context of COVID-19. In this study, we aim to identify interventions that can improve domestic violence victims' mental health amid the COVID-19 pandemic to address the research gap. Main text Drawing insights from established COVID-19 review frameworks and a comprehensive review of PubMed literature, we obtained information on interventions that can address domestic violence victims' mental health challenges amid COVID-19. We identified practical and timely solutions that can be utilized to address mental health challenges domestic violence victims face amid COVID-19, mainly focusing on (1) decreasing victims' exposure to the abuser and (2) increasing victims' access to mental health services. Conclusion Domestic violence is a public health crisis that affects all demographics and could result in significant morbidity and mortality. In addition to emphasizing mental health challenges faced by domestic violence victims, multidisciplinary interventions are identified that could provide timely and practical solutions to domestic violence victims amid the pandemic, which range from tailored shelter home strategies, education programs, escape plans, laws and regulations, as well as more technology-based mental health solutions. There is a significant need for more multipronged and multidisciplinary strategies to address domestic violence amid and beyond the pandemic, particularly interventions that could capitalize on the ubiquity and cost-effectiveness of technology-based solutions.